Analisis Indikator Sociability pada Placemaking Gedung Filateli Jakarta - Mawardini, Tsara Dhinna (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
The use of a placemaking approach in the transformation of Gedung Filateli Jakarta into a creative space is one of the efforts to revitalize cultural heritage buildings. As a creative space, Gedung Filateli Jakarta must meet a number of indicators. This article aims to identify and analyze the application of socialization indicators in the placemaking of Gedung Filateli Jakarta. The method used is scheduled observations at Gedung Filateli Jakarta. The phenomena found during the observation will be analyzed using sociability indicators. Based on research that has been done on the placemaking of Gedung Filateli Jakarta, especially the great hall, terrace, and pedestrian areas, it has succeeded in accommodating various types of activities for visitors with varied backgrounds so as to produce various social interactions. The three areas of at Gedung Filateli Jakarta are actively used for various program activities including music performances, fashion shows, product exhibitions and regular visits. These findings have succeeded in validating the application of sociability indicators in Gedung Filateli Jakarta which describes the social position of Gedung Filateli Jakarta towards visitors as a creative public space. As a creative space, Gedung Filateli Jakarta is a placemaking object that can encourage social interaction